The Relationship Between Storey of Buildings and Fall Risk - Tsai, Ching-Yao; Lin, En-Sheng; Li, Yang-Tzu; Tung, Tao-Hsin; Chen, Wei-Cheng (Frontiers in Public Health, 2021)
Abstract Purpose. This study examined the association between storey of building and fall risk in older adults’ residences and residents’ level of fear of falling. Methods. The National Health and Aging Trends Study(NHATS) collected information that would provide an understanding of basic trends people aged 65 years and older. Using a longitudinal survey, the present study employed the first round of NHATS data that was collected in 2011. In the first round, 12,411 participants were enrolled, and 8,077 interviews were completed. The study sample sizes for falling and worry about falling are 6,153 and 6,142, respectively. Results. Subjects lived in single storey of building had higher prevalence for fall or worry about falling compared with the subjects live in multi-storey. Conclusion.Several clinical factors independently were indicated pertaining to the fall and worry about falling in older adult’s residences.